ADAB SEBAGAI FONDASI PROFESIONALISME GURU: ANALISIS PEMIKIRAN IBNU JAMA’AH AL-SYAFI’I DALAM PERSPEKTIF MANAJEMEN PENDIDIKAN ISLAM - Nursalam Siradjuddin; Samsuddin; Muhammad Naji Bulloh; Agusman (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the concept of adab (ethical conduct) of teachers in the thought of Ibn Jama'ah and to explain its position as the foundation of teacher professionalism from the perspective of Islamic educational management. This research employs a qualitative approach using a library research method. The primary source is Ibn Jama'ah’s Tadzkirat al-Sāmi‘ wa al-Mutakallim fī Adab al-‘Ālim wa al-Muta‘allim, while secondary data are drawn from literature on Islamic education, educational management, and teacher professionalism. The data were analyzed using content analysis and thematic analysis techniques. The findings reveal that adab in Ibn Jama'ah’s thought functions as a value system that shapes teachers’ orientation, integrity, competence, and leadership. Adab serves not only as the foundation of pedagogical, professional, social, and personal competencies but also as the basis for educational leadership and continuous professional development. Based on the synthesis of the findings, this study proposes an Adab-Based Teacher Professionalism Model consisting of four main pillars: professional spirituality, moral-scientific integrity, humanistic pedagogical competence, and educational leadership. This model offers a new perspective for developing teacher professionalism in Islamic education that is more holistic, integrative, and value-based.